Chile : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that the Chilean economy is enjoying a broad-based upswing, fueled by a strong global environment and buoyant domestic demand. Underpinned by supportive fiscal and monetary policies, GDP growth is expected to reach 5 3/4 percent in 2007, above the estimated potential growth rate of about 5 percent. Buoyant credit growth and strengthening labor market conditions continue to boost consumer spending and solid corporate profits. The authorities have advanced a broad structural reform agenda. The government has also launched initiatives to boost education, strengthen job-specific human capital, and promote innovation.